2017
DOI: 10.1016/j.nlm.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of high intensity exercise and the Val66Met polymorphism on circulating BDNF and locomotor learning

Abstract: Brain-derived neurotrophic factor (BDNF) has been directly related to exercise-enhanced motor performance in the neurologically injured animal model; however literature concerning the role of BDNF in the enhancement of motor learning in the human population is limited. Previous studies in healthy subjects have examined the relationship between intensity of an acute bout of exercise, increases in peripheral BDNF and motor learning of a simple isometric upper extremity task. The current study examined the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 52 publications
2
62
3
1
Order By: Relevance
“…HIIT also improved walking endurance and balance, although MICE yielded similar improvements . Several potential mechanisms for improved mobility have been proposed in the literature including increased corticospinal excitability and neurotrophin expression, which enhance motor learning . Among individuals with stroke, aerobic exercise may also promote neuroplasticity and neuroprotection .…”
Section: Discussionmentioning
confidence: 94%
“…HIIT also improved walking endurance and balance, although MICE yielded similar improvements . Several potential mechanisms for improved mobility have been proposed in the literature including increased corticospinal excitability and neurotrophin expression, which enhance motor learning . Among individuals with stroke, aerobic exercise may also promote neuroplasticity and neuroprotection .…”
Section: Discussionmentioning
confidence: 94%
“…This finding agrees with recent work from our lab that found that high intensity exercise also did not promote locomotor learning in neurologically intact adults (Helm et al . ). Moreover, these findings, in both those with stroke and neurologically intact adults, differ from previous studies of the effect of exercise on upper extremity skill learning.…”
Section: Discussionmentioning
confidence: 97%
“…; Helm et al . ). Briefly, on session 1, we collected blood samples from all subjects to quantify changes in lactate and BDNF concentrations in response to exercise priming.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The potential benefits of this type of exercise on other, more complex motor tasks, involving multi‐joint movements of lower limbs, such as those required for locomotion, are less well established (Helm et al . ). Furthermore, most previous studies demonstrating that acute exercise can improve motor memory and skill learning have involved young, healthy individuals.…”
mentioning
confidence: 97%